Seni Pementasan Tari Kidang Edan Sebagai Ungkapan Religiusitas Masyarakat Desa Adat Sekumpul - I Wayan Gata; Putu Cory Candra Yhani (Jnanasidanta, 2021)
The variety and style of dance is a crystallization of the cultural values of the supporting communities. The art of Balinese dance can be classified into three groups, namely: Wali Dance, which is the art of dance that is performed in temples and in places that have something to do with religious ceremonies that function as means or implementers of religious ceremonies. Bebali dance, which is a dance that functions as an accompaniment to ceremonies and ceremonies that take place in a temple or outside a temple which in its performance uses a play, Balih-balihan Dance, which is all dance arts that have elements and the basis of noble dance arts. Every region in Bali has different artistic traditions, both in terms of the type of art and its meaning. Art traditions in each region in Bali have their own uniqueness which is always preserved because the life of a work of art, whether in the form of dance or drama, is closely related to the life of religious ceremonies. One of the very unique traditions in Bali, especially in the Sekumpul Village, is the performance of the Kidang Edan Dance which is held during the pujawali religious ceremony. In addition to the Kidang Edan Dance, it is a sacred dance that is believed from generation to generation by the people of the Sekumpul Village. Kidang Edan Dance is manifested as a form of gratitude to Ida Sang Hyang Widhi Wasa for the gift given to the people of Sekumpul Village.